Ulnar variance and skeletal maturity of radius and ulna in female gymnasts - Beunen, G.; Malina, R. M.; Claessens, A. L.; Lefevre, F. J.; Thomis, M. (Medicine & Science in Sports & Exercise, 1999)
Ulnar overgrowth is not apparently associated with advanced maturity of the distal radial epiphysis as defined in protocols for assessing skeletal maturity and does not apparently lead to premature epiphyseal closure of the distal radius.